Implementasi Good Governance Di Indonesia - Nur, Mohamad Ichsana; Handayani, Fitri Andalus (Publica: Jurnal Pemikiran Administrasi Negara, 2019)
The good governance promoted by the World Bank and UNDP still has no a definitive agreement. This concept is more interpreted as a solution for the realization of effective and efficient government performance. Furthermore, the World Bank as a donor provides assistance to countries to build institutional capacity and training for public officials to improve their competence. The methodology in this study employes descriptive qualitative data collection techniques with literature review. The good governance as a concept reaps criticism in its implementation, one of the criticisms given is the lack of control in the implementation of good governance in governmental actors. Not only that the application of good governance in a country is often forced, even though the principle does not fit into the existing government system, state, culture of society. In Indonesia case in terms of Good Governance implementation, there are still many problems such as bureaucratic reform that is not good, practices of KKN, demands for the application of good governance principles which among them are not in accordance with the local characteristics of the Indonesian people, and the participation is still low.